Application of a low-angle light scattering technique to cell volume and cell signaling studies on Ehrlich ascite tumor cells. Issue 2 (2006) - Zinchenko Zinchenko, Valeriy P. Valeriy P.; Lee Lee, Vyacheslav V. Vyacheslav V.; Berezhnov Berezhnov, Alexey V. Alexey V.; Mindukshev Mindukshev, Igor V. Igor V.; Jenkins Jenkins, Richard O. Richard O.; Goncharov Goncharov, Nikolay V. Nikolay V.
Abstract : A method for studying cells based on low-angle light scattering was applied to cell volume and cell signaling studies on Ehrlich ascite tumor cells (EATC). Changes in the volume of EATC were measured in hypotonic medium, as well as after activation with exogenous ATP, ionomycin and thimerosal. Increase of [Ca 2+ ]i under ATP and ionomycin action induced reversible changes of cell volume: fast shrinking was followed by swelling. Thimerosal caused a reversible change in EATC volume with high amplitude; endoplasmic reticulum played the key role in this response. Having obtained kinetic parameters of changes in cell volume under activation of the cells, quantitative measurements of K +, Na + and anion flows responsible for this process can then be obtained. In spite of some fundamental differences in the behavior of cells of different dimensions there are many similarities, and there is a good theoretical background for dealing with both small and large cells.